2019
DOI: 10.1136/bmjopen-2018-028705
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with breast cancer screening participation among women in mainland China: a systematic review

Abstract: ObjectivesAlthough detecting breast cancer at an early stage through screening has been clearly shown to be an effective strategy, the screening participation rate in China remains low. This systematic review sought to synthesise the current evidence to identify factors associated with breast cancer screening participation among women in mainland China.DesignThis study was a systematic review.Data sourcesStudies were collected from PubMed, PsycINFO, CINAHL, EMBASE and three major Chinese databases, specially C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 28 publications
(52 reference statements)
3
50
1
2
Order By: Relevance
“…This characteristic of the women, however, became statistically nonsignificant after controlling for other predictors. Although we found no relationship between place of residence and breast cancer screening in a multivariate model, a systematic review of 19 papers on breast cancer screening among women in China suggested that living in urban areas positively predict participation in breast cancer screening [15].…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…This characteristic of the women, however, became statistically nonsignificant after controlling for other predictors. Although we found no relationship between place of residence and breast cancer screening in a multivariate model, a systematic review of 19 papers on breast cancer screening among women in China suggested that living in urban areas positively predict participation in breast cancer screening [15].…”
Section: Discussioncontrasting
confidence: 92%
“…Globally, gender also is a key predisposing factor for all types of cancers, with women having a higher likelihood than men [7]. Studies have also found that a lack of participation in social groups is associated with a lower likelihood of breast cancer screening among women [9,10,11,12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Accessibility is one of the important factors associated with breast cancer screening participation [ [10] , [11] , [12] ]. Outreach programs increase accessibility for community residents to receive a mammography.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors may affect the performance of BC screening behaviors [ 16 , 17 , 18 , 19 , 20 ]. In the literature, it states that, in addition to sociodemographic and cultural characteristics, health beliefs related to the disease and its consequences affect health behaviors by increasing the motivation of individuals [ 21 ].…”
Section: Introductionmentioning
confidence: 99%